The Relationship of Socio-Demographic Factors, Fertility Behavior and Child's Perceived Value with Fertility Intention of Women in a Region in the East of Iran - Elham Azmoude; Haniye Behnam; Saeede Barati-Far; Maryam Kabirian (Shiraz University of Medical Sciences, 2017)
Background: Fertility intention is one of the strongest predictors of couple's fertility behavior that is affected by many variables. This study aimed to identify the relationship of socio-demographic factors, fertility behavior, and child's perceived value with fertility intention of women in a region in the east Iran Methods: In this descriptive cross-sectional study, 241 married women aged between 15 and 49 years of Torbat Heydariyeh City in 2015, were studied. The data collection scales included a demographic information form, fertility information questionnaire and Trommsdorff's child value questionnaire. Data were analyzed using SPSS 16 by Chi-square, Kruskal-Wallis, t-independent test and logistic regression. The significance level of P<0.05 was considered. Results: Most of the subjects (52.7%) had no fertility intention. Independent-samples test and Kruskal-Wallis revealed significant differences in fertility intention with the subject's age, mate's age, number of children and costs of children (P=0.001). In addition, in subjects with children of both sexes, intention for childbearing was significantly lower when compared to subjects with only one sex in children (P=0.001). However, when the logistic regression test was performed, being housewife, number of children, having children of both sexes, benefit and costs of children showed statistical significance (P<0.05). Conclusion: The results indicate that being housewife, number of current children, having children of both sexes, and perceived childbearing costs are important in determining the odds that a woman will intend to have a child. These findings can contribute to the realization of new population programs towards higher fertility rate in the country.